Monitoring Kualitas Air Kolam Ikan Lele Berbasis IoT - Saputra, Zanu; Silalahi, Parulian; Verentinus, Steven; Safitri, Wulan (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
The application of Internet of Things (IoT) technology in catfish pond water quality monitoring systems is very important to support the success of cultivation. This research aims to design an IoT-based system capable of monitoring temperature, pH, and ammonia parameters in real-time to ensure optimal water conditions. The methods used include the design and integration of hardware such as temperature, and pH with ESP32 module, as well as software development using MIT App Inventor and Arduino IDE for data monitoring through applications and web platforms. The test results show that the system has a high level of accuracy, with an average accuracy of 99.78% on the pH sensor and 99.89% on the temperature sensor. The data collected in real-time is displayed on the LCD screen and can be accessed through the mobile application, making it easier to manage the pool. The system activate automatic equipment such as aerators and pumps to efficiently address unsuitable conditions. The application of IoT to catfish pond water quality monitoring has successfully improved operational efficiency and enabled management that is more responsive to environmental changes.